1972
DOI: 10.1161/01.res.31.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Vascular Responses to Stimulation of Chemoreceptors and Baroreceptors: EVIDENCE FOR REFLEX ACTIVATION OF VAGAL CHOLINERGIC INNERVATION

Abstract: Coronary vascular responses to stimulation of chemoreceptors were studied in anesthetized, artificially ventilated dogs. The circumflex coronary artery was perfused at constant flow so that changes in perfusion pressure reflected changes in coronary resistance. Practolol, a myocardioselective beta-receptor antagonist, and pacing were used to minimize indirect effects of myocardial responses on coronary resistance. Carotid and aortic injections of nicotine produced decreases in coronary perfusion pressure avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 19 publications
6
33
1
Order By: Relevance
“…29 ' 30 Electrical stimulation of the carotid sinus nerve, which mimics increased carotid sinus pressure, produces inhibition of coronary sympathetic constrictor tone. 31 ' 32 In the present experiments a restriction of flow and oxygen delivery was observed before a-receptor blockade but not afterwards; the most probable interpretation of these results is that an a-receptor vasoconstrictor mechanism limits coronary blood flow during reflex sympathetic activation from the carotid sinus baroreceptors.…”
Section: Neural Controlsupporting
confidence: 48%
“…29 ' 30 Electrical stimulation of the carotid sinus nerve, which mimics increased carotid sinus pressure, produces inhibition of coronary sympathetic constrictor tone. 31 ' 32 In the present experiments a restriction of flow and oxygen delivery was observed before a-receptor blockade but not afterwards; the most probable interpretation of these results is that an a-receptor vasoconstrictor mechanism limits coronary blood flow during reflex sympathetic activation from the carotid sinus baroreceptors.…”
Section: Neural Controlsupporting
confidence: 48%
“…The coronary vasodilatation seen in the present study is similar to that which has PULMONARY CHEMOREFLEX AND CORONAR Y RESISTANCE 287 been observed previously during carotid sinus nerve stimulation (Hackett, Abboud, Mark, Schmid & Heistad, 1972), peripheral chemoreceptor stimulation (Hashimoto, Igarashi, Uei & Kumakura, 1964;Vatner & McRitchie, 1975;Vatner, 1983;Murray, Lavallee & Vatner, 1984), carotid sinus baroreceptor stimulation (Ito & Feigl, 1985), and the Bezold-Jarish reflex (Feigl, 1975). Further, the neurohumoral basis for the changes in coronary resistance evoked by capsaicin in the present study is comparable to that seen in previous studies.…”
Section: G a Ord Wa Y And K H Pitettisupporting
confidence: 91%
“…Further, the neurohumoral basis for the changes in coronary resistance evoked by capsaicin in the present study is comparable to that seen in previous studies. Hackett et al (1972) stimulated the carotid sinus nerve in animals whose hearts were paced, and observed a reflex coronary vasodilatation that was diminished by the administration of atropine. Similarly, Vatner (1983) has shown that the coronary vasodilatation associated with stimulation of peripheral chemoreceptors is mediated by both an increase in cholinergic activity and a decrease in a-adrenergic tone.…”
Section: G a Ord Wa Y And K H Pitettimentioning
confidence: 99%
“…First of all, in the present investigation the cerebral circulation was left intact and the carotid chemoreceptor reflex was stimulated without inducing cerebral hypoxia. It has been shown by Jacobs et al (3) and Hackett et al (23), that intracarotid nicotine or cyanide stimulates primarily the carotid chemoreceptor reflex. It is also felt that central nervous system stimulation did not occur, because after ipsilateral carotid sinus nerve section, no change in systemic or LV function was observed with intracarotid nicotine or cyanide.…”
Section: * Discussionmentioning
confidence: 97%